Bunian People: Myths, Perceptions and Impressions of Behavior and Culture in Minangkabau - Sirait, Grace Angel; Lingga, Yesna Enika Br; Harahap, Rosmawaty (CV. Rayyan Dwi Bharata, 2024)
Minangkabau has a unique and diverse culture, starting from art, culture, songs, fairy tales, poetry, beliefs, characterizations and visual characters. One of the unique things about Minangkabau is that it is a belief that is widely known by the public and has been discussed from time to time until now. One of the interesting beliefs in Minangkabau is about the Urang Bunian mythology, however, the lack of understanding of the target audience and the lack of optimal media in conveying information about Urang Bunian visualizations are the main factors for the author to design the Urang Bunian character design in Minangkabau culture through the Art Book media. Urang Bunian was made in the form of an Art Book media which contains about creating character designs from the information obtained. Apart from the Art Book media, the delivery of this information is also supported by several other media which help the main media to introduce the subject to the target audience, namely posters, stickers, t-shirts, tote bags, holograms, x-banners, mini x-banners. The design method used is the 5w+1h approach, namely what, who, when, where, why and how. By using the 5w+1h theory, all aspects summarized in the character design design process can be created through Art Book media